2011
DOI: 10.1104/pp.111.174805
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Pht1;5 Mobilizes Phosphate between Source and Sink Organs and Influences the Interaction between Phosphate Homeostasis and Ethylene Signaling    

Abstract: Phosphorus (P) remobilization in plants is required for continuous growth and development. The Arabidopsis (Arabidopsis thaliana) inorganic phosphate (Pi) transporter Pht1;5 has been implicated in mobilizing stored Pi out of older leaves. In this study, we used a reverse genetics approach to study the role of Pht1;5 in Pi homeostasis. Under low-Pi conditions, Pht1;5 loss of function (pht1;5-1) resulted in reduced P allocation to shoots and elevated transcript levels for several Pi starvation-response genes. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
217
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(225 citation statements)
references
References 83 publications
6
217
0
2
Order By: Relevance
“…In Arabidopsis, overexpression of AtPht1;5 led to increases of root hair numbers and length both under Pi-sufficient and Pi-deficient conditions, while silencing of the gene did not have a significant effect on root hair development (Nagarajan et al, 2011). It was remarkable that the OsPT1-Ri lines, particularly OsPT1-Ox lines, developed much longer and dense root hairs only under P-replete conditions (Fig.…”
Section: Ospt1 Functions In Pi Acquisition and Distribution And Pi-mementioning
confidence: 96%
See 3 more Smart Citations
“…In Arabidopsis, overexpression of AtPht1;5 led to increases of root hair numbers and length both under Pi-sufficient and Pi-deficient conditions, while silencing of the gene did not have a significant effect on root hair development (Nagarajan et al, 2011). It was remarkable that the OsPT1-Ri lines, particularly OsPT1-Ox lines, developed much longer and dense root hairs only under P-replete conditions (Fig.…”
Section: Ospt1 Functions In Pi Acquisition and Distribution And Pi-mementioning
confidence: 96%
“…It has been shown that AtPht1;1 and AtPht1;4, which were most highly expressed in epidermis and root hair cells, contributed to Pi transport into roots during growth in a wide range of external Pi concentrations (Shin et al, 2004), while AtPht1;5, which showed Pi deficiency-induced expression specifically in the phloem cells of older leaves, cotyledons, and flowers (Mudge et al, 2002), functions in mobilizing Pi between source and sink organs (Nagarajan et al, 2011). That the OsPT1 promoter directed its constitutive expression in epidermis, cortex, and stele cells of various rice tissues (Fig.…”
Section: Ospt1 Functions In Pi Acquisition and Distribution And Pi-mementioning
confidence: 99%
See 2 more Smart Citations
“…Loss-of-function mutants of AtPHT1;5 and transgenic lines overexpressing this gene in Arabidopsis were developed to demonstrate its role in Pi mobilisation between source and sink under different Pi conditions (Nagarajan et al 2011). Little is known about the roles of PHT1 genes in P loading into grains in cereals such as wheat and barley.…”
Section: Low-affinity Transporters and Organelle Pi Transportersmentioning
confidence: 99%